Wirausaha Pendidikan Dalam Bidang Jasa Kursus Bahasa Inggris - Septi Romanika; Prita Gusti Juliani; Putrisari Napitupulu; Besus Maulana Sulthon (JPM: Jurnal Pengabdian Masyarakat, 2021)
At this time there is still a lack of public awareness of the importance of being able or fluent in English. In addition, the price of the course is also a consideration for the community, and the time is flexible. This English course is a solution for people who want to learn and can speak English. To introduce this English course to the public at this time only use the distribution of brochures through social media. So that there are still many people who are not familiar with this English course. Thus, a wider promotion is needed through the website. This English course also has many learning programs that the community can choose according to their respective ages and targets, the time of course learning can be adjusted according to the wishes of each student. This English course teacher is also experienced in his field. The teaching and learning system for this English course is not only able to learn online via zoom, but the teacher can go to each student's home to teach English according to student requests. This English course learning method also utilizes multimedia developments, so that learning becomes more fun and easy to understand. This English course business has progressed with the increase in students every month starting in February reaching 20%, March reaching 35%, and April reaching 25%. The overall income earned by this English course business which is calculated from each program attended by each student reaches 80%. The research aims to examine the progress of entrepreneurship in English courses, there are several determinants of entrepreneurship in English courses that can be internal and external.